FRANKFURT TABLE AS AN EXAMPLE OF GOOD PRACTICES OF BUSINESS ETHICS IN TOURISM - Jurišin, Ljubica; Dragin, Aleksandra; Pivac, Tatjana; Košić, Kristina; Blešić, Ivana (Turizam, 2019)
The purpose of this paper was to analyze the Frankfurt Table, as a successful tool in the development of business ethics in global tourism. The aim of the research was to examine the form and use of the Frankfurt Table and to investigate the situation in Serbia, in terms of whether this list is used as a guide in the business of travel agencies. In this regard, the attitudes of employees in travel agencies in Serbia were examined. During the collection, analysis and interpretation of the results, historical, comparative, descriptive methods, as well as survey research and synthesis were used. The results of the research can be useful to the tourism industry, to numerous participants whose services are part of the tourist arrangement.